Langfristige Auswirkungen von Sprunggelenksorthesen auf sportspezifische Fertigkeiten im Handball - Jerosch, J.; Thorwesten, L.; Haverkämper, U. (Sportverletzung Sportschaden, 1998)
We documented the effect on sports specific capabilities of long lasting wear of ankle braces in 14 handball players. For a period of 4 months half of the team performed all athletic activities with an ankle brace. The other players served as control performing the same athletic activities without wearing a brace. For documentation of the coordinative capabilities a special jump-test with a COMET-system was used. This test was performed after a standardised warm-up at the beginning and at the end of the 4 months observation period with and without an ankle brace. The results showed that wearing the used ankle brace for a period of 4 months did not lead to a negative effect on jumping capabilities. The brace group showed even an increased ability in the used test. This could be documented in short as well as long term effects. CONCLUSION: Long wear of ankle braces do not lead to negative side-effects in sports specific capabilities that are represented by the performed jump-test.